CURRENT TRAINING ACTIVITIES AND CONTINUOUS TRAINING NEEDS OF VILLAGE HEALTH WORKERS IN BAC NINH PROVINCE (Vietnam Journal of Community Medicine, 2026)
Objectives: To describe the current training activities and continuous training needs of village health workers in Bac Ninh province.Method: A cross-sectional descriptive study was conducted among 456 village health workers in Bac Ninh.Results: The majority of village health workers (97.8%) had participated in professional training courses during the two years since 2023, of which 93.4% lasted only 1-2 days. Training on the application of health information technology for reporting and statistics was received by only 46.7% of participants. All nine core professional domains and all 50 clinical techniques stipulated in Circular No. 27/2023/TT-BYT were rated as “high priority” training needs. Among these, the top priorities were: basic first aid (priority gap A - B = 2.1 points), application of health information technology in reporting and statistics (2.0 points), and safe use of essential medicines (1.96 points).Conclusion: There needs to be close coordination between authorities at all levels, the health sector, training institutions, village health workers and relevant organizations to develop, implement and monitor flexible, highly practical continuing education programs that ensure resources and meet practical needs.
Keywords: Need, continuous training, village health workers, Bac Ninh.